Perspektif Hukum Islam Tentang Implementasi Wakaf Produktif Dalam Pemberdayaan Ekonomi Umat - Syaripudin, Enceng Iip; Nurhuda, Rano (Jurnal Hukum Ekonomi Syariah, 2024)
Productive management of waqf assets has been proven to provide sustainable economic benefits for the community, such as building hospitals, schools, training centers and empowering micro businesses. However, there are still several obstacles in managing productive waqf, such as limited resources, low public understanding, and a lack of supporting regulations. This research aims to analyze the implementation of productive waqf in empowering the people's economy based on an Islamic legal perspective. Waqf is an Islamic economic instrument that has great potential in improving community welfare. However, the implementation of productive waqf in Indonesia is still not optimal. The research method used is library research with a qualitative approach. Using a qualitative approach, this research examines the implementation of productive waqf in various waqf management institutions, and analyzes its conformity with the principles of sharia economic law. The research results show that the implementation of waqf is productive from an Islamic legal perspective, in line with the principles of maslahah (benefit) and maqashid sharia (the goals of Islamic law). Productive waqf can improve the economic welfare of the people in a sustainable manner, as well as encourage the improvement of strategic sectors such as education, health and economic empowerment of underprivileged communities. Therefore, more intensive efforts are needed to optimize the management of productive waqf in Indonesia, both from regulatory, institutional and community empowerment aspects.  Keywords: Islamic Law; Implementation; Productive Waqf; Community Economy;